Pengaruh Aktivitas Pasar Terhadap Kinerja Ruas Jalan Guntur di Pasar Rakyat Oro-Oro Dowo Kota Malang - Dicky Umbu Deki Sipul; Andy Kristafi Arifianto; M. Sadillah (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2025)
Traditional market activities often cause an increase in vehicle traffic, which impacts the performance of surrounding roads. The Oro-Oro Dowo People's Market in Malang City is one such economic hub with high activity intensity, potentially causing side effects and congestion on Jalan Guntur, the main access road to the market. This study aims to analyze the performance of Jalan Guntur and examine the impact of Oro-Oro Dowo Market activities on traffic conditions on this road. This study uses a quantitative approach through field surveys to obtain primary data in the form of traffic volume, side obstacles, and road geometric characteristics. Observations were conducted for seven days during the market's operating hours. Road performance analysis was conducted using the 2023 Indonesian Road Capacity Guidelines (PKJI) method, including road capacity calculations, saturation levels, and road service levels. The results of the study show that market activities have a significant impact on the performance of the Guntur Road section. Traffic volume increases during rush hour, especially on weekends. The highest saturation degree value recorded was 0.86 on Sunday, indicating that the road service level was in category E, meaning that traffic conditions were approaching maximum capacity and had the potential for congestion. The dominant side obstacles were caused by parking on the road, pedestrian activity, and loading and unloading activities by traders. Based on the research results, it can be concluded that the activities of the Oro-Oro Dowo Market significantly reduce the performance of the Guntur Road section. Therefore, efforts are needed in the form of parking arrangements, control of side obstacles, and the application of traffic engineering to improve the smoothness and performance of roads in the market area.